Plasma spray dried on the perfomance of super early weaned piglets - Natália Yoko Sitanaka; Renato Pacheco Monferdini; Fábio Enrique Lemos Budiño; José Evandro de Moraes; Alessandra Marnie Martins Gomes de Castro; Fernando Gomes de Castro Junior (Boletim de Indústria Animal, 2015)
Aiming to evaluate the effect of plasma spray dried (PSD) on the performance of super early weaned piglets, an experiment was carried out in the Pig’s farming sector of the Institute of Animal Science and Pasture, at Nova Odessa, São Paulo State. Fifty six piglets were used, homogeneous as for the lineage, weighing 3.87±0.65kg approximately with average age of 14 days, distributed in a completely randomize experimental design with four treatments, seven replicates and two animals per experimental unit. It was tested four levels of plasma inclusion on piglet’s diets into two consecutive periods, 14 to 28 days of age (first period); 29 to 42 days of age (second period). The plasma levels utilized were 0%, 2%, 4% and 6% for the first period and 0%, 1%, 2% and 3% for the second period. Into the third period (42 to 56 days of age) all the piglets were feed with no PSD. The performance of the piglets was evaluated by biweekly weighing and in the last day of experiment, when the age of allotment was equal to 56 days. The analyzed variables aiming to evaluate the performance of the animals were the average daily feed intake (DFI), average daily weight gain (ADG), and feed conversion (FC). No significant differences were observed (P>0.05) for weight gain, food intake and feed conversion. As a conclusion to the carried out experiment, it is suggested that animals fed with plasma spray dried has no additional benefits in its performance.